A Prospective Survey of Skin Manifestations in Children With Inborn Errors of Immunity From a National Registry Over 17 Years - Al-Herz, Waleed; Zainal, Mohammad; Nanda, Arti (Frontiers in Immunology, 2021)
Background and objectives: Reports on skin manifestations in Inborn Errors of Immunity (IEI) are based on retrospective analysis, small series or isolated case reports. The present prospective study aimed to determine the spectrum of skin manifestations in children with IEI and their relevance to specific molecular defects. Methods: The data were obtained from the Kuwait National Primary Immunodeficiency Disorders Registry during the period of 2004 - 2020. Results: 313 pediatric cases of IEI, 71% were diagnosed at molecular level, were registered with a cumulative follow-up period of 29734 months. Skin manifestations were seen in 40.3% of the patients and they were among the presenting manifestations in 33%. Patients with skin manifestations were older at both onset and diagnosis ages of IEI symptoms, but this was statistically significantce for the later only. The diagnosis delay was significantly longer in patients with skin manifestations. There was a statistically significant association between having skin manifestations and IEI category, being more common in patients with complement deficiencies, combined immunodeficiencies, and diseases of immune dysregulation. There was no statistically significant association between having skin manifestations and both gender and survival. Skin infections were the most frequent manifestations followed by eczema, and autoimmune associations. Among IEI with more than 10 cases, skin lesions were a consistent finding in DOCK8 deficiency, Hyper IgE syndrome, Ataxia-telangiectasia, and RAG1 deficiency. Conclusions: Skin manifestations are common in IEI patients and they had significant diagnosis delay and referral to the specialists. Improvement of awareness about IEI is needed among pediatricians and dermatologist.